2010
DOI: 10.1152/ajpheart.00656.2009
|View full text |Cite
|
Sign up to set email alerts
|

Competition of pyruvate with physiological substrates for oxidation by the heart: implications for studies with hyperpolarized [1-13C]pyruvate

Abstract: Carbon 13 nuclear magnetic resonance (NMR) isotopomer analysis was used to measure the rates of oxidation of long-chain fatty acids, ketones, and pyruvate to determine the minimum pyruvate concentration ([pyruvate]) needed to suppress oxidation of these alternative substrates. Substrate mixtures were chosen to represent either the fed or fasted state. At physiological [pyruvate], fatty acids and ketones supplied the overwhelming majority of acetyl-CoA. Under conditions mimicking the fed state, 3 mM pyruvate pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
71
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 57 publications
2
71
0
Order By: Relevance
“…The technique provides unique insights into important questions regarding myocardial metabolism, substrate preference, pharmacological intervention, and the ability to differentiate between normal and pathological metabolism [22][23][24][25][26][27][28][29][30][31][32][33]. Pyruvate is by far the most widely used hyperpolarized 13 C substrate and it can be served as a probe for mitochondrial oxidative flux [34].…”
Section: Introductionmentioning
confidence: 99%
“…The technique provides unique insights into important questions regarding myocardial metabolism, substrate preference, pharmacological intervention, and the ability to differentiate between normal and pathological metabolism [22][23][24][25][26][27][28][29][30][31][32][33]. Pyruvate is by far the most widely used hyperpolarized 13 C substrate and it can be served as a probe for mitochondrial oxidative flux [34].…”
Section: Introductionmentioning
confidence: 99%
“…With the recent enhancements in the MR sensitivity of the 13 C nucleus achieved using dynamic nuclear polarisation (DNP) (1), it is now possible to complement structural data using MRI with global metabolic information in the myocardium (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Work with several in vivo animal models has combined DNP with different imaging techniques (18)(19)(20)(21)(22), including chemical shift imaging (CSI) (23), to obtain metabolic maps of the heart using hyperpolarised [1-13 C]pyruvate (2,20,(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the work described here was to develop a combined DNP and CSI protocol for application in the isolated perfused rat heart to generate metabolic images of hyperpolarised [1][2][3][4][5][6][7][8][9][10][11][12][13] (5,13). It should be possible to generate maps of these metabolites in the isolated perfused rat heart and to use the metabolic images of [1- 13 C]pyruvate as a marker of tissue perfusion, [1][2][3][4][5][6][7][8][9][10][11][12][13] C]lactate as a marker of anaerobic metabolism and [ 13 C]bicarbonate as a marker of aerobic metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isotopomer analysis of extracts from the freeze-clamped hearts indicated that acetate was the preferred substrate for energy production, glucose contribution to energy production was minimal, and anaplerosis was stimulated in the presence of propionate. Under conditions where production of acetyl-CoA is dominated by the availability of an alternative substrate, acetate, propionate markedly stimulated PDH flux as detected by the appearance of hyperpolarized (25,27). Consequently, in addition to disease processes, physiological fluctuations in the concentrations of fatty acids also influence the appearance of HP […”
mentioning
confidence: 99%